Jumanji : the next level [videorecording (Blu-Ray)] - Kasdan, Jake, 1975-; Johnson, Dwayne, 1972-; Black, Jack, 1969-; Hart, Kevin, 1979-; Jonas, Nick; Glover, Danny; DeVito, Danny; Van Allsburg, Chris (Sony Pictures Home Entertainment, 2020)
The gang is back, but the game has changed. As they return to Jumanji to rescue one of their own, they discover that nothing is as they expect. The players will have to brave parts unknown and unexplored, from the arid deserts to the snowy mountains, in order to escape the world's most dangerous game.